EVALUASI KINERJA RUAS JALAN AKIBAT PENERAPAN SISTEM JALAN SATU ARAH MENGGUNAKAN SIMULASI MIKROSKOPIK PTV VISSIM (STUDI KASUS: JALAN IMAM BONJOL KOTA BANDAR LAMPUNG) - Siti Rahma; Michael; Aulia Maharani; Ayu Kamila Khanza; Siska Apriwelni (LPPM Universitas Abdurrab, 2025)
This study evaluates the existing conditions of the Jalan Imam Bonjol along with the three intersections’ performance located within the corridor. The existing condition of the road segment was analyzed using PKJI 2023. The degree of saturation was found to be 0.38 on weekdays, while it was 0.52 on weekends. Although the road segment is not saturated yet, the operational speed data on weekdays show values of 5.3 km/h in the east–west direction and 4.9 km/h in the west–east direction. Meanwhile on weekends, the operational speeds are 6.4 km/h in the east–west direction and 4.9 km/h in the west–east direction. The operational vehicle speeds during peak hours are below the average speed of urban roads according to PKJI 2023, which is 20–50 km/h. Therefore, this study implements a traffic engineering by applying one-way system on one of the intersection approaches, namely Jalan Pisang, through microscopic simulation using the PTV VISSIM. The simulation of the existing condition shows the operational average speed reached 7.43 km/h, average delay was 11.31 seconds, and the average queue length was 4.04 m. Meanwhile, the one-way system simulation on Jalan Pisang resulted in significant changes, namely the average speed reached 7.62 km/h, the average delay amounted to 9 seconds, and the average queue length was equal to 3.82 m. This indicates that the traffic engineering scenario has the potential to improve the performance of the road segment and intersections.